Factors that influence the adoption and implementation of sustainable procurement: a case of a South African public university - Mpapha, Sive (Rhodes University, Faculty of Commerce, Rhodes Business School)
Climate change and resource scarcity have become some of the world's most critical problems and are among the most significant megatrends influencing world leaders' agendas in decision- making (Rothkopf & Casey, 2014; International Social Security Association, 2014). Sustainable procurement has been identified as one of the strategic tools that can resolve these issues to help the world move towards a more sustainable and resilient future (World Bank, 2019). Through sustainable procurement practices, organisations can meet their demand and supply of goods and services while minimising environmental harm, maximising financial returns, and enhancing socioeconomic status (Villena & Gioa, 2020; Bonnemaison, Eldandsson, Ibach & Spiller, 2021). This qualitative research used an Eastern Cape-based higher education institution in South Africa as a case study to investigate factors that influence adopting and implementing sustainable procurement, with resilience as a theoretical foundation, in higher education. The research obtained approval from the participating university as a gatekeeper for the study; it began by drafting a research proposal and securing ethical clearance from Rhodes University. Semi-structured interviews were used with seven higher education procurement staff members to get the data working in procurement in higher education. The findings from the study revealed that managerial support and knowledge of sustainable procurement were determining factors for whether or not a university developed and implemented a strategy for sustainable procurement.Secondly, the participants mostly cited barriers as inadequate financial resources resulting in limitations for the university, therefore partially implementing sustainable practices. Thirdly, the data revealed that university staff in procurement had a basic understanding of sustainable procurement.
Keywords: Sustainable procurement; Universities and colleges -- South Africa -- Eastern Cape; Organizational resilience; Implementation science